PERANAN UAV (UNMANNED AERIAL VEHICLE) DALAM IDENTIFIKASI ANCAMAN LONGSOR TINGGI DI SUNGAI CI DURIAN, DAERAH CIGUDEG, BOGOR - M Farrel Anugerah; Elisabet Dwi Mayasari (Jurnal Saintifik, 2022)
Technological developments in the field of photography, especially in the manufacture of 3D models from a collection of aerial photographs can be quickly and effectively with Unmanned Aerial Vehicle (UAV). This research was conducted in CI Durian River as the target object of 3D modeling. The study area located in Bogor regency, West Java province has a morphology of hills to low hills with winding rivers and composed by the Bojongmanik formation (Tmb). The dominant rock units in the study area are sandstone and claystone. The process of data retrieval using Unmanned Aerial Vehicle (UAV) can be used to perform mapping quickly and accurately at a more affordable cost. This research uses descriptive and interpretive methods. Primary Data in the study is all the data acquired through drones. Secondary Data are data such as slope maps and topographic maps. Primary Data and secondary data can be a reference in detecting landslides in the study area. The tool used in this study is to use unmanned Aerial Vehicle (UAV) technology in the form of drones by utilizing aerial photography data which is then processed into Digital Elevation Model (DEM) data. The use of Ground Control Point (GCP) can certainly add accuracy to the creation of DEM data. The Data is a reference in the interpretation of the threat of landslides that occurred in the study area. Primary data in the form of slope can validate secondary data in the form of slope maps. The dominant factors that influence the threat of landslides in the study area include: topographic factors and steep slopes. Topography and slope factors are very steep slopes are the main factors of high landslide threat in the study area.